The International Conference on Health Informatics ICHI 2013, Vilamoura, Portugal on 7-9 November, 2013 - Zhang, Yuan-Ting.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This volume presents the proceedings of the International Conference on Health Informatics (ICHI). The conference was a new special topic conference initiative by the International Federation of Medical and Biological Engineering (IFMBE), held in Vilamoura, Portugal on 7-9 November, 2013. The main theme of the ICHI2013 was (3z(BIntegrating Information and Communication Technologies with Biomedicine for Global Health(3y(B. The proceedings offer a unique forum to examine enabling technologies of sensors, devices and systems that optimize the acquisition, transmission, processing, storage, retrieval of biomedical and health information as well as to report novel clinical applications of health information systems and the deployment of m-Health, e-Health, u-Health, p-Health and Telemedicine.s
Towards Unobtrusive and Wearable Blood Pressure Measurements -- Monitoring and Screening of Vulnerable Patients with Acute Cardiovascular Diseases -- Photo-acoustic Imaging and its Applications -- Tele-healthcare Systems and Applications -- Body Sensor Networks for Emerging Health Informatics -- Privacy and Network Security -- Emerging Technologies and Applications in Telemedicine -- Advanced Solutions for Supporting Cardiac Patients in Rehabilitation -- RFID & Wireless Sensors for Ubiquitous Healthcare & Internet-of-Things -- Public Health Informatics.
Keywords: Engineering; Medical records -- Data processing; Telecommunication; Biomedical engineering; Engineering; Biomedical Engineering; Health Informatics; Health Informatics; Communications Engineering, Networks